2005
DOI: 10.1121/1.1872312
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tones on speaking frequency and intensity ranges in Mandarin and Min dialects

Abstract: The differences of speaking frequency and intensity in different tonal dialects has not been widely investigated. The purposes of this study were (1) to compare the speaking frequency and speaking intensity ranges of Mandarin and Min and (2) to compare the speaking frequency and intensity ranges of Mandarin and Min to those of American English. The subjects were 80 normal Taiwanese adults divided into two dialect groups, Mandarin and Min. The speaking F0, the highest speaking F0, the lowest speaking F0, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 23 publications
(14 reference statements)
2
32
0
2
Order By: Relevance
“…The range of fundamental frequency and intensity used in speaking Min mainly depends upon the high-low tone combination [3,7,18,19] . Chen [20] proposed that the speaking frequency and speaking intensity ranges for Min speakers were greater than those in other studies for American English speakers [20] . Everyday conversation of Min dialect may provide a greater chance of vocal training on frequency and intensity which may result in greater physiological frequency and physiological intensity ranges for Min speakers than for nontonal language speakers.…”
Section: Introductionmentioning
confidence: 93%
“…The range of fundamental frequency and intensity used in speaking Min mainly depends upon the high-low tone combination [3,7,18,19] . Chen [20] proposed that the speaking frequency and speaking intensity ranges for Min speakers were greater than those in other studies for American English speakers [20] . Everyday conversation of Min dialect may provide a greater chance of vocal training on frequency and intensity which may result in greater physiological frequency and physiological intensity ranges for Min speakers than for nontonal language speakers.…”
Section: Introductionmentioning
confidence: 93%
“…An example of the former would be studies looking at the scaling of tones in the phonetic realization of intonation, where a central issue is how to capture tonal invariance in the face of variation in pitch range (e.g., Dilley and Brown, 2007;Hirschberg and Ward, 1992;Liberman and Pierrehumbert, 1984). Examples of the latter include clinical studies investigating the extent to which various clinical populations have atypical prosody (e.g., Diehl, Watson, Bennetto, Mcdonough, and Gunlogson, 2009;Hubbard and Trauner, 2007), studies of the vocal correlates of affect (e.g., Banse and Scherer, 1996;Ladd, Silverman, Tolkmitt, Bergmann, and Scherer, 1985;Sobin and Alpert, 1999), and studies of various speaker-oriented factors such as the effects of age, gender, height and weight, ethnicity, and regional accent on f0 (Chen, 2005;Deutsch, Le, Shen, and Henthorn, 2009;Hollien, Hollien, and de Jong, 1997;Nishio and Niimi, 2008;Van Bezooijen, 1995;Van Dommelen and Moxness, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum range of speaking intensity for Taiwanese females and males was 25.3-26.7 dB greater than non-tonal language English speakers of their comparative genders [19] . The difference in maximum range of speaking intensity between Taiwanese and Americans may also be due to the tonal effects of Mandarin [33] . In voice range profiles, the lowest frequency and the highest frequency for females were significantly greater than for males, which was mainly due to vocal fold length and stiffness difference in the two genders [2,3,6] .…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the maximum range of speaking fundamental frequency of this study and studies of other languages and races for adult females and males ( table 3 ) demonstrated that the maximum range of speaking fundamental frequency in reading for Taiwanese females and males was 4.8-10.3 semitone greater than non-tonal language American and Swedish speakers of their comparative genders [10,11,17,19] . The difference in maximum range of speaking fundamental frequency between Taiwanese and other languages can be explained by the tonal effects of Mandarin [33] , in which the frequency range of the four basic tones in words and sentences was reported to be 154-258% wider than that of English [46] and possibly Swedish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation